EDUKASI INTERAKTIF KESEHATAN REPRODUKSI DAN KEBERSIHAN LINGKUNGAN MENUJU GENERASI SEHAT BERSAMA SDN SUKOSARI 1 - Eky Madyaning Nastiti; Wahyu Kurniawan; Sely Tri Wahyuni; Fakhirah Ghina Ramadhani; Alwiya Kinanti; Caca Engellina; Icha Dilla Pratiwi; Aurelia Reyza Safitri; Nabila Kamalia; Dwi Qurratul Aini; Muhammad Husni Mubarok; Nazahwa Intan Tamara; Mahardika Putri Wahyudinanti; David Kurnia Sandi (Jurnal SADEWA, 2026)
Elementary school children who are approaching adolescence are in a very important phase of development in forming healthy lifestyle habits such as environmental hygiene and understanding their own bodies. At SDN Sukosari 1, particularly in grade VI, students still lack sufficient understanding of these issues. The objective of this activity is to provide education and increase the knowledge of grade VI students regarding reproductive health and environmental hygiene. The activity was attended by 40 sixth-grade students, using interactive educational methods such as PowerPoint presentations, health posters, simulations, and discussions. Based on the post-test results, 33 out of 40 students achieved perfect scores, and it is hoped that this activity will provide benefits in their daily lives. The application of interactive educational methods directly using visuals and discussions effectively increases students' understanding of reproductive health and environmental cleanliness